Some common and less known Phaneropterinae (Orthoptera: Tettigoniidae; Phaneropterinae) with the description of a new species from India - Nagar, Rajendra; Swaminathan, R.; Mal, Jhabar (Zootaxa, 2015)
The present paper deals with the description of eleven katydids of the tettigonid subfamily Phaneropterinae (Tettigoniidae). The katydids of more common occurrence in different parts of India include: Phaneroptera gracilis Burmeister, Ducetia japonica (Thunberg), Himertula pallisignata Ingrisch and Shishodia, Isopsera peducnulata Brunner von Wattenwyl, and Trigonocorypha unicolor Stal; while those lesser known are Phaneroptera myllocerca Ragge, Himertula kinneari (Uvarov), Elimaea melanocantha (Walker), Elimaea carispina (Ingrisch and Shishodia), and Trigonocorypha angustata Uvarov. Record of a new species of the genus Ducetia, named as Ducetia serratus sp. nov., is mentioned. The key diagnostic morphological characters have been supported with photographs and illustrations of the body parts: head, pronotum, stridulatory file and the genitalia (supra-anal plate and sub-genital plate). A key to identify the species of the reported katydids has been provided.